2012
DOI: 10.1371/journal.pone.0039792
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity of the Mycobacterium tuberculosis Beijing Family Based on SNP and VNTR Typing Profiles in Asian Countries

Abstract: The Mycobacterium tuberculosis (MTB) Beijing strain is highly virulent, drug resistant, and endemic over Asia. To explore the genetic diversity of this family in several different regions of eastern Asia, 338 Beijing strains collected in Taiwan (Republic of China) were analyzed by mycobacterial interspersed repetitive unit-variable number tandem repeat (MIRU-VNTR) typing and compared with published MIRU-VNTR profiles and by the Hunter-Gaston diversity index (HGDI) of Beijing strains from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 34 publications
3
28
0
Order By: Relevance
“…The close historical relationship between China (39) and Japan (17) might be responsible for the BJ sublineages in Thailand. The most frequently identified strains in Taiwan were similar to predominant BJ subtypes in our populations, including ST10 (35.42%), ST19 (29.65%), and ST22 (13.46%) (40). Advanced means of global travel could affect the spread of infectious strains among countries, and bacterial adaptation raises concern over transnational transmission.…”
Section: Discussionmentioning
confidence: 57%
“…The close historical relationship between China (39) and Japan (17) might be responsible for the BJ sublineages in Thailand. The most frequently identified strains in Taiwan were similar to predominant BJ subtypes in our populations, including ST10 (35.42%), ST19 (29.65%), and ST22 (13.46%) (40). Advanced means of global travel could affect the spread of infectious strains among countries, and bacterial adaptation raises concern over transnational transmission.…”
Section: Discussionmentioning
confidence: 57%
“…One possible underlying reason is that Beijing lineage in China originated in the North, while the Euro American lineage originated in the South. Previous studies reported that the high genetic diversity of Beijing genotypes in Japan is consistent with their likely origin in this region, indicating a more ancient common ancestor for the Beijing genotype strains in North-Eastern Asia [27,28]. Conversely, some studies have detected Beijing (like) strains with a full spoligotyping pattern and a RD105 deletion or “extended” RD105 deletion in Southwest of China, which would be consistent with the common ancestor of the currently expanding Beijing strains originating from this region [23,29].…”
Section: Discussionmentioning
confidence: 76%
“…It is still the leading cause of death among all communicable infectious diseases despite a steady decline in both incidence and mortality rates since 1950. Previous studies indicate that the most prevalent Mycobacterium tuberculosis (MTB) strains in Taiwan belong to the Beijing lineage, followed by East African-Indian (EAI) and Haarlem strains [ 2 , 3 ]. Notably, EAI strains in northern Taiwan comprise about 11% of MTB isolates, whereas in southern Taiwan they comprise up to 32% [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%